PRE-COLONIAL POLITICAL ADMINISTRATION IN THE NORTH CENTRAL NIGERIA: A STUDY OF THE IGALA POLITICAL KINGDOM - Audu, Jacob (European Scientific Journal, ESJ, 2014)
Available evidence has shown that pre-colonial African societies had a formal and organized system of government before the advent of colonialism. However, there seem to be an intellectual conspiracy against the minor ethnic groups as most of the contemporary literature has focused on the three major ethnic groups-Hausa/Fulani, Yoruba and the Igbo political systems. In order to save these minor ethnic groups from political extinction, this paper attempt a discourse on the pre-colonial political administration of the North Central Nigeria ; a study of the Igala political kingdom. The study relied on secondary data to generate data for this study. The paper is structured into different but interrelated compartment. The paper found out that in about the second decade of the 17th century, the process of the evolution of dynastic rule which started in the 16thCentury had become consolidated under Ayegba Om’Idoko and as such this marked our starting point. The paper concludes that Igala political kingdom was the only most powerful kingdom between the 16th -18th century after defeating the Jukuns, Binis and Hausa /Fulani jihadists. In the light of this, the Igala political kingdom cannot be left in the oblivion but must be acknowledged and documented for political history and posterityy.